2016
DOI: 10.4103/0019-5049.177869
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of post graduate students on objective structured clinical examination in Anaesthesiology: A preliminary report

Abstract: Background and Aims:The scenario in medical education is changing with objective structured clinical examination (OSCE) being introduced as an assessment tool. Its successful implementation in anaesthesiology postgraduate evaluation process is still limited. We decided to to evaluate the effectiveness of OSCE and compare it to conventional examinations as formative assessment tools in anaesthesiology.Methods:We conducted a cross-sectional comparative study in defined population of anaesthesiology postgraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…Regarding the quality of OSCE performance, more than half the respondents reported being fully aware of the nature of the exam (54%), but scores for the remaining parameters were considerably low, ranging between 23.5% and 28.8%. This was in accordance with that found by Dharma in 2014, 23 and in contrast to the results of various other studies 18, 19, 24. Students' perception regarding the validity and reliability of OSCE scoring ranged between ‘neutral’ to ‘agree to a great extent’.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the quality of OSCE performance, more than half the respondents reported being fully aware of the nature of the exam (54%), but scores for the remaining parameters were considerably low, ranging between 23.5% and 28.8%. This was in accordance with that found by Dharma in 2014, 23 and in contrast to the results of various other studies 18, 19, 24. Students' perception regarding the validity and reliability of OSCE scoring ranged between ‘neutral’ to ‘agree to a great extent’.…”
Section: Discussionsupporting
confidence: 90%
“…A similar difference of opinion was also observed between students (41.7%) and examiners (11.1%) in a study conducted by Omu et al11 in Kuwait. Some studies have raised concerns that time was a problem and suggested that they focus on restricting time but rather should concentrate on how well students can perform 38,39. However, Schoonheim-Klein et al40 demonstrated that increased time per station had no impact on student’s performance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we hope that the data presented here will enable higher powered studies to be conducted in the future. Finally, although OSCE style assessments are widely-regarded as the gold-standard method of clinical skills assessment [ 24 , 25 ], it must be remembered that they can never be truly representative of a hospital or ward environment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%